Crimean-Congo Hemorrhagic Fever: A Re-emerging Zoonosis - Ozdan Akram Ghareeb; Awni Ismail Sultan (An Overview of Disease and Health Research Vol. 2, 2025)
One of the public health challenges is the control of Crimean-Congo hemorrhagic fever (CCHF), as this viral zoonotic disease infects both animals and humans, sometimes leading to death. In 2016, prevalence rates were between 20 and 30% in Iraq, Iran and Turkey in cattle, camels and sheep. CCHF has been identified as potentially endemic throughout Africa, Asia and the Middle East. The re-emergence of this endemic disease in certain regions, including Iraq, has highlighted the need for more documented information and reliable data regarding its transmission, infection patterns, and prevention strategies. The aim of this review is to discuss the taxonomy and structure of the causative virus, mode of transmission, clinical forms, and possible prevention of infection. The causative virus consists of a globular RNA genome particle with a segmented negative-sense encapsulated in a lipid structure containing or in direct contact with infected viral glycoproteins. Infection usually occurs by ticks, human or animal tissue, or blood. The causative virus has a high ability to transmit Infection in areas with mammals, whether large or small, such as rabbits and cattle. Animals are asymptomatic, while in people it is manifested by high fever and ends with hemorrhagic syndrome. The key measure to achieving prevention for this infection is avoiding tick bites by applying acaricides in livestock production farms. It is recommended to implement preventive measures to control tick vectors in endemic countries, and to encourage collaboration between clinical veterinarians, physicians and ecologists’ researchers.